Impact of perampanel on pharmacokinetics of concomitant antiepileptics in patients with partial‐onset seizures: pooled analysis of clinical trials. (10th May 2016) - Majid, Oneeb; Laurenza, Antonio; Ferry, Jim; Hussein, Ziad
Abstract : Aims: To evaluate the impact of perampanel and demographics on clearance of concomitant antiepileptic drugs (AEDs), in patients with refractory partial‐onset seizures. Methods: Pooled data from three Phase III clinical studies with adjunctive perampanel were used. Blood samples for evaluation of 11 concomitant AEDs were taken during baseline (before perampanel initiation), and at weeks 10, 14, and 19 during the maintenance phase of perampanel treatment (2–12 mg/day, once daily at bedtime). Models estimating apparent clearance of each concomitant AED were fitted to the data, and the effects of perampanel and demographic variables on clearance were determined. Final models were assessed with goodness of fit plots including population predictions and individual predictions against observations. Results: No significant impact of perampanel on clearance was found for clonazepam ( n  = 81), levetiracetam ( n  = 330), phenobarbital ( n  = 54), phenytoin ( n  = 90), topiramate ( n  = 226) or zonisamide ( n  = 93). Statistically significant, but small and not clinically relevant increases in model‐predicted clearance were detected for carbamazepine (+4.3% with 12 mg perampanel; n  = 379), clobazam (+3.4% males, +7.7% females, 12 mg; n  = 114), lamotrigine (+9.3%, 12 mg; n  = 356), and valproic acid (+5.0%, 12 mg; n  = 349). Oxcarbazepine clearance was reduced (26%; n  = 200), but the clinical relevance is unclear as levels of the active metabolite (the monohydroxy derivative of oxcarbazepine) were not measured. Conclusions: Population PK data show that perampanel (2–12 mg/day, once daily at bedtime) has no relevant impact on the clearance of the most commonly used concomitant AEDs.